Males, Outcrossing, and Sexual Selection in Caenorhabditis Nematodes - Cutter, Asher D. (Genetics, 2019)
Males of Caenorhabditis elegans provide a crucial practical tool in the laboratory, but, as the rarer and more finicky sex, have not enjoyed the same depth of research attention as hermaphrodites. Males, however, have attracted the attention of evolutionary biologists who are exploiting the C. elegans system to test longstanding hypotheses about sexual selection, sexual conflict, transitions in reproductive mode, and genome evolution, as well as to make new discoveries about Caenorhabditis organismal biology. Here, we review the evolutionary concepts and data informed by study of males of C. elegans and other Caenorhabditis. We give special attention to the important role of sperm cells as a mediator of inter-male competition and male–female conflict that has led to drastic trait divergence across species, despite exceptional phenotypic conservation in many other morphological features. We discuss the evolutionary forces important in the origins of reproductive mode transitions from males being common (gonochorism: females and males) to rare (androdioecy: hermaphrodites and males) and the factors that modulate male frequency in extant androdioecious populations, including the potential influence of selective interference, host–pathogen coevolution, and mutation accumulation. Further, we summarize the consequences of males being common vs rare for adaptation and for trait divergence, trait degradation, and trait dimorphism between the sexes, as well as for molecular evolution of the genome, at both micro-evolutionary and macro-evolutionary timescales. We conclude that C. elegans male biology remains underexploited and that future studies leveraging its extensive experimental resources are poised to discover novel biology and to inform profound questions about animal function and evolution.